Is virtual bronchoscopy useful for physicians practising in a district general hospital?. Issue 945 (14th July 2004) - Dheda, K; Roberts, C M; Partridge, M R; Mootoosamy, I
Abstract : Background: Virtual bronchoscopy software is now available to district general hospitals (DGHs). There is limited information on the clinical utility of virtual bronchoscopy and whether it offers any additional information over conventional axial computed tomography in the setting of a busy DGH chest unit. Methods: Virtual bronchoscopy and computed tomography findings were compared in all patients who had a virtual bronchoscopy study over a 12 month period. Results: Eighteen consecutive patients had virtual bronchoscopy for a specific clinical indication over the study period. Additional information was conveyed by virtual bronchoscopy in five patients (in four patients the airways distal to an obstruction were better visualised thereby influencing decisions about airway stenting and in one patient the virtual bronchoscopy study showed an endobronchial lesion missed on computed tomography). In nine patients who were unfit for fibreoptic bronchoscopy (FOB) the radiologist was more confident in excluding an obstructive airway lesion. The main indication for performing a virtual bronchoscopy study was to rule out an obstructive airway lesion in patients who were unfit for FOB (n = 11). Conclusion: Virtual bronchoscopy is feasible and useful in the management of a few selected patients in a DGH chest unit. Virtual bronchoscopy may convey additional information over computed tomography when the distal airways need to be visualised and for discrete endoluminal lesions.